Association of comprehensive evaluation scores with in-hospital mortality in critical geriatric patients in a national reference hospital in Peru. - Portugal-Sánchez , José W. (2024)
Objective: To evaluate the association of comprehensive assessment scores with mortality in geriatric patients of a national reference hospital in Peru. The study: A prospective cohort study was conducted. Patients over 60 years of age were included during the period from November 1, 2021 to June 30, 2022. The data was collected from the clinical history. SOFA, KATZ, FAST and Charlson Index scores were included to evaluate the association with mortality. Findings: 93 participants were found.The prevalence of mortality was 32.3%. In the simple regression, an association was observed between SOFA score greater than or equal to 12 (RR:15.3), FAST score (RR:2.29) and the Charlson index (RR:2.46) with intrahospital mortality. In the multiple regression adjusted for age and sex, only the SOFA score maintained statistical significance (RR: 13.42 p<0.001).  Conclusion: The SOFA score has a strong association with in-hospital mortality in geriatric patients admitted to an intensive care unit in Peru.